Minimising the risk of extensor pollicis longus rupture following volar plate fixation of distal radius fractures: a cadaveric study - Perry, DC (The Royal College of Surgeons of England, 2010)
INTRODUCTION: Rupture of extensor pollicis longus (EPL) tendon is a recognised complication following volar plate fixation of distal radius fractures, usually from attrition caused by prominent screws. We sought to identify the screw holes in some of the most commonly used plates which may precipitate tendon injury. SUBJECTS AND METHODS: Three fixed-angle volar locking plates were sequentially positioned into 18 cadaveric arms. A wire was passed through each of the holes in the plates using a locking guide and the dorsal relationships noted. RESULTS: Each plate had specific ‘high-risk’ holes which directed the wire towards the EPL groove. The central screw holes appeared mostly implicated in EPL injury. CONCLUSIONS: Awareness of ‘high-risk’ holes and appropriate minor alterations in surgical technique may consequently decrease the incidence of EPL irritation and rupture.